Evaluation of Architectural Elements and Sensory Comfort in the Visitor Experience of Culinary Tourism Centers in Surabaya - Harmunisa, Yusvika Ratri; Sunarya , Wendy; Utomo, Heru Prasetiyo; Putra, Rulliannor Syah (Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Culinary tourism centers are not only places to enjoy food but also function as public spaces that provide social and spatial experiences for visitors. The quality of the built environment and architectural elements contribute to the level of comfort, perception, and user preferences for a place. Research examining the relationship between architectural elements, sensory comfort, and visitor experience in public culinary spaces, particularly in tropical areas and government-managed facilities, is still limited. This study aims to evaluate the influence of architectural elements on sensory comfort and visitor experience at the Wiyung Culinary Tourism Center, Surabaya. The study used a mixed methods approach with a sequential explanatory strategy. The quantitative stage was carried out by distributing Likert-scale questionnaires (1–4) to 120 respondents, then analyzed using Pearson's validity test and Cronbach's Alpha reliability test. The qualitative stage was carried out through field observations, interviews, and visual documentation to deepen the results of the quantitative analysis. The results showed that the facade and decorative elements play a role in shaping visual appeal and visitors' initial impressions. The quality of ventilation and lighting are the main factors influencing thermal comfort and visit duration. The qualitative analysis also revealed that spatial arrangement contributes to ease of orientation and social activities in the Culinary Tourism Center area.